1993
DOI: 10.1213/00000539-199301000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Convective Warming Therapy Does Not Increase the Risk of Wound Contamination in the Operating Room

Abstract: Although convective warming therapy is effective in preventing hypothermia in anesthetized patients, little is known concerning the potential risks of its use. Hence, this balanced cross-over study was designed to determine if the use of convective warming therapy increased the risk of wound contamination. For 4 h, eight healthy male volunteers (aged 20-25 yr) lay supine on an operating room table with their lower bodies and legs covered with a warming cover and sterile surgical drape. The convective warming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The effect of FAW on contaminant counts in the sterile OR environment ( 12 , 25 , 26 , 31 ) generated different opinions among different authors. Studies conducted by Albrecht et al found an increased bacterial load in OR room with ultra clean ventilation (UCV) when FAW is used, and attributed this effect to the floor level location of FAW blowers and their intake, where most of the contaminants originated ( 4 , 6 , 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of FAW on contaminant counts in the sterile OR environment ( 12 , 25 , 26 , 31 ) generated different opinions among different authors. Studies conducted by Albrecht et al found an increased bacterial load in OR room with ultra clean ventilation (UCV) when FAW is used, and attributed this effect to the floor level location of FAW blowers and their intake, where most of the contaminants originated ( 4 , 6 , 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…25 In addition, we were unable to consider all factors that have been associated with SSI, as the details of blood transfusion, obesity, incontinence and fitness for surgery, which have been identified elsewhere as important predictors for deep infection, 4,18 were not sufficiently detailed in the medical record. Moreover, prior research is limited to a handful of studies that have either looked at the disruption in ventilation due to forced-air warming in conventional operating theatres 26,27 or evaluated accumulation microbial contamination and emission issues. [28][29][30][31][32] Research in ultra-clean operating theatres is limited to a single orthopaedic study in which forcedair warming resulted in elevated microbial counts over the surgical site.…”
Section: Fig 6bmentioning
confidence: 99%
“…It was previously reported that a singular use of warming coverlets does not increase the potential for airborne bacterial wound infection (7). Nevertheless in some institutions convective air coverlets are being reused, although not recommended by any of the manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study it was shown that a single use of a convective air-warming coverlet did not increase the potential for wound contamination (7). Yet, in some instances these coverlets may come in direct contact with the surgical site perioperatively and in some institutions covers are being reused on several different patients (which is not in accordance with use recommended by manufacturers).…”
mentioning
confidence: 99%